A Comparative Study of the Proto-Semitic Root nẓr - Odendaal, Willem Johan (1966)
Thesis presented for the Master’s Degree in Semitic Languages at the University of Stellenbosch. Examiners: F. C. Fensham, L. M. Muntingh, P. J. van Zijl; spez. 4-103: The Manifestations of nẓr in Akkadian; 104-120: in Ugaritic.